New Media-Based Environmental Campaign: Sekumpul Waste Bank (Sekumpul Bank Sampah) in Empowering the Community’s Ecomony - Muhammad Alif; Sri Astuty; Lalita Hanief (Jurnal Nomosleca, 2024)
Department of Public Housing, Residential Areas and the Environment (DPRKPLH) Banjar Regency (2022) the amount of waste entering final disposal sites reached 290 tons per day, an increase of 60 tons compared to the previous year. The Sekumpul Waste Bank in Banjar Regency actively carries out environmental campaigns via social media Instagram about Reuse, Reduce and Recycle. The aim of this research is to analyze new media-based environmental campaigns for community economic empowerment at the Sekumpul waste bank. The method used in this research is a descriptive qualitative approach. Data collection techniques were interviews, literature studies and documentation with a total of 2 informants. The data analysis technique uses Manual Data Analysis Procedure (MDAP), namely daily notes, transcripts, coding, categories, themes and memos. The results show that the Sekumpul Waste Bank campaigns for waste management through Instagram posts, holding events and providing material on local radio broadcasts. It is hoped that this environmental campaign can increase community participation in managing waste wisely and with economic value.